Adopsi Inovasi Pelayanan Publik Berbasis Website “Disdukcapilbisa” Di Dinas Kependudukan Dan Pencatatan Sipil Kota Batam Pada Masa Pandemi Covid-19 - Wahyu Andrean; Mayarni Mayarni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Adoption of innovation is a procedure for implementing a new idea carried out by an agency, then the idea is communicated through various channels and certain time frames in the social system. One of the innovations adopted by the Batam City Population and Civil Registration Service is the DISDUKCAPILBISA internet site which was adopted from the Surabaya City Population and Civil Registration Service called E-Lampid. The application of innovation is very beneficial for all parties, both the community and the service that provides population administration services during the Covid-19 pandemic, but it is known that there are still obstacles in the process of adopting the innovation. This review aims to see the innovation adoption process carried out by the Batam City Population and Civil Registration Office from beginning to end with indicators: knowledge stage, persuasion stage, decision-making stage, implementation stage and confirmation stage. This study uses qualitative research methods with data collection techniques using observation, interviews and documentation. This study has results that indicate that the adoption of innovations carried out by the Batam City Population and Civil Registry Office has been running quite well but there are still obstacles in the process so that the implementation of this innovation is still not optimal.